Project-based learning through augmented reality-assisted math trails at Blenduk Church to promote mathematical literacy - Nugroho, Muhammad Andi; Yulandari, Indriana; Cahyono, Adi Nur (Jurnal Elemen, 2024)
Mathematical literacy ability is one of the indispensable abilities in the development of mathematics education today. Currently, the mathematical literacy ability of students in Indonesia is still low. In the field of education, the era of society 5.0 has a great impact, so education must be able to produce human resources who have good mathematical literacy and are able to apply technology well with their literacy abilities. This study aims to determine how the quality of a project-based learning model with math trails assisted by augmented reality in the context of Blenduk Church is able to promote students' mathematical literacy. The research method used is design research. The data were analysed using qualitative and quantitative data analysis techniques. Qualitative data analysis techniques were used to analyse the results of student response questionnaires after conducting project-based learning with augmented reality-assisted math trails at Blenduk Church. Meanwhile, quantitative analysis techniques are used to analyse students' mathematical literacy skills obtained from student test results before and after conducting project-based learning with augmented reality-assisted math trails at Blenduk Church. However, further research is needed on the development of augmented reality-assisted learning instruments and media in other contexts to promote students' literacy skills.